2021
DOI: 10.7717/peerj.10801
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of two fluorescence immunoassays for the rapid detection of SARS-CoV-2 antigen—new tool to detect infective COVID-19 patients

Abstract: Background Real-Time Reverse-Transcription Polymerase Chain Reaction (RT-PCR) is currently the only recommended diagnostic method for SARS-CoV-2. However, rapid immunoassays for SARS-CoV-2 antigen could significantly reduce the COVID-19 burden currently weighing on laboratories around the world. Methods We evaluated the performance of two rapid fluorescence immunoassays (FIAs), SOFIA SARS Antigen FIA (Quidel Corporation, San Diego, CA, USA) and STANDARD F COVID-19 Ag FIA (SD Biosensor Inc., Gyeonggi-do, Repu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…These numbers can be confirmed by other studies(Dinnes et al, 2021) and compare well with our findings. The manufacturer of Standard F indicates a higher sensitivity and specificity of 93.70% and 99.63% respectively (SD Biosensor, 2021a) which is supported by a study by Porte et al (90.6% and 96.9%)(Porte et al, 2021). These differences between trial and real-world data can be explained with bias due to test application and its evaluation under study conditions.…”
mentioning
confidence: 54%
“…These numbers can be confirmed by other studies(Dinnes et al, 2021) and compare well with our findings. The manufacturer of Standard F indicates a higher sensitivity and specificity of 93.70% and 99.63% respectively (SD Biosensor, 2021a) which is supported by a study by Porte et al (90.6% and 96.9%)(Porte et al, 2021). These differences between trial and real-world data can be explained with bias due to test application and its evaluation under study conditions.…”
mentioning
confidence: 54%
“…All studies were written in English, except for 3 in Spanish [53, 62, 134], 1 in Turkish [95], and 1 in French [153]. Out of the 196 studies, 26 conducted a case-control study [21, 32, 34, 66, 67, 72, 81, 84, 88-90, 93, 94, 96, 103, 108, 135, 140, 144, 145, 151, 156, 166, 168, 182, 184], while the remaining 168 were cross-sectional or cohort studies. The reference method was RT-PCR in all except 1 study, which used viral culture [135].…”
Section: Resultsmentioning
confidence: 99%
“…This quite likely results from the on average low viral load in 1 study [49], and the asymptomatic study population in the other [175]. On the contrary, compared to the other studies unusual high sensitivity was found in studies where average viral load was high [45, 84, 144, 145] or participants were mainly within the first week of symptom onset [42, 54, 135].…”
Section: Discussionmentioning
confidence: 99%
“…When the viral load decreased with C T values above 25, no test presented a sensitivity greater than 15% except the Vircell automatic reader, which detected 36.4% of the samples with C T values of ≥25. The automatic reading of the fluorescent signal can be more sensitive than visual inspection of some of the RATs, which may account for the higher sensitivity of the Vircell assay for samples with a low viral load ( 17 , 18 ).…”
Section: Discussionmentioning
confidence: 99%